How do appraisal as threat or challenge, efficacy, and environmental quality affect wellbeing in the COVID-19 pandemic? - Wallis, Hannah; Holzen, Veronique; Sieverding, Theresa; Matthies, Ellen; Schmidt, Karolin (Frontiers in Psychiatry, 2023)
Background In crises, it is of great relevance to identify mechanisms that help people to maintain a certain level of wellbeing. This paper investigates whether appraising the COVID-19 pandemic as a threat vs. as a challenge has different effects on subjective wellbeing during the pandemic. Furthermore, we study the role of the perceived local environmental quality for individuals' subjective wellbeing. Methods Via online survey study with two times of measurement (N = 758), we investigated (a) the prediction of participants' wellbeing in June 2020 and June 2021 through five variables and (b) how these five variables moderated within-participant differences in subjective wellbeing over time. Results Results showed that a stronger perception of the pandemic as a threat (feeling worried) and a lower education in June 2020 predicted a lower subjective wellbeing in 2020 and 2021. A stronger challenge appraisal (feeling confident), higher efficacy expectations, and positive perceptions of the local environmental quality in June 2020 predicted a higher wellbeing in 2020 and 2021. There was no substantial change in participants' aggregated wellbeing over time. However, those who perceived the pandemic more as a threat in June 2020 struggled more with negative changes in their wellbeing, whereas those who perceived the pandemic more as a challenge reported a higher wellbeing. Conclusion It seems key to support people in activating positive feelings to successfully cope with crises.